Brass'Art in Molenbeek: stadslaboratorium voor “samen doen” - Nadia Fadil; Maryam Kolly (Brussels Studies)
This paper takes the case of the Brass'Art cultural café located on the municipal square of Molenbeek, as a starting point for a study aimed at understanding the construction of a common urban space with a pluralistic purpose. Based on an ethnographic study between May 2017 and January 2018, this article aims to show how the presence of alcohol in this space mobilises and concentrates diverse and even contradictory repertoires – of a discursive, ethical and emotional nature – behind the creation of public space. The Brass'Art case study reflects at the micro and local level the implications of the coexistence of agents with different religious sensitivities and orientations. According to a pragmatic methodology, this paper tries to demonstrate that the fine tuning of the balance of power between the majority and the minority takes place not so much through conscious negotiations or strategies of “civic indifference”, but through practical adjustments in keeping with the principle of community relations.